Fiduciary Accountability And Factors Contributing To Sustainablity Business Growth Of Malaysian Indian Smes - M Sesha Salam, Lakshmi Gandhan (2022)
This study addresses the impact of fiduciary accountability of managers, entrepreneurial orientation, market orientation, social-media, and sustainable business growth under the mediating effect of innovation on Malaysian Indian SMEs. Based on the resource-based view and the dynamic capabilities perspective, this study developed a conceptual model to collaborate the relationships. Additionally, this study investigated the mediating effect of innovation on the four aforesaid independent variables or relationships. As part of the study, data was collected through structured questionnaire from sampling of Malaysian Indian SMEs data base obtained from the Indian business organisations. The sampling method used was purposive, which generated 204 respondents who were Indian SMEs data base obtained from Indian business organisations. Data collected was analysed by means of using both IBM SPSS and SmartPLS-3.3. The empirical finding, to a large extent, confirmed the research model, and supported twelve out of thirteen direct hypotheses. These included: a) fiduciary accountability was positively related to sustainable business growth; b) entrepreneurial orientation was positively related to sustainable business growth; c) marketing orientation was positively related to sustainable business growth; d) social-media was positively related to sustainable business growth; e) fiduciary accountability was positively related to innovation; g) entrepreneurial orientation was positively related to innovation; h) marketing orientation was positively related to innovation; and i) social-media was positively related to innovation.